2019
DOI: 10.1007/s12630-019-01334-7
|View full text |Cite
|
Sign up to set email alerts
|

Abusive behaviour in Canadian and US operating rooms

Abstract: Background Disruptive intraoperative behaviour has detrimental effects on clinicians, institutions, and patients. Abusive behaviour is an egregious form of disruptive behaviour that has a particular risk of detrimental consequences. The prevalence of abusive behaviour in the operating room (OR) is uncertain. We therefore examined the prevalence and frequency of exposure to abusive behaviour in a cohort of Canadian and US OR clinicians. Methods This was a sub-study of an international survey examining disruptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Operating rooms in the United States and Canada have been found to be affected by uncivil behaviors. In a recent survey of 7,465 operating room staff in the United States (US) and Canada, 667 staff members stated that they had experienced abuse on a personal level and 1,121 clinicians had witnessed the abuse of colleagues [4]. An international survey of 7,465 operating room workers found that 98% were exposed to some form of disruptive behavior in the surgical setting, with an estimated average of 64 exposures to operating room disruptions per year [5].…”
Section: Introductionmentioning
confidence: 99%
“…Operating rooms in the United States and Canada have been found to be affected by uncivil behaviors. In a recent survey of 7,465 operating room staff in the United States (US) and Canada, 667 staff members stated that they had experienced abuse on a personal level and 1,121 clinicians had witnessed the abuse of colleagues [4]. An international survey of 7,465 operating room workers found that 98% were exposed to some form of disruptive behavior in the surgical setting, with an estimated average of 64 exposures to operating room disruptions per year [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ce compte rendu révélait que 23 % des cliniciens de SOP avaient été personnellement victimes d'abus et 39 % avaient été témoins de comportements abusifs. 7 Dans le troisième manuscrit, publié dans ce numéro, 4 un groupe pré-spécifié des répondants internationaux (4775 personnes de sept pays) ont répondu à des questions liées au signalement des comportements perturbateurs aux administrateurs de l'hôpital. La quasi totalité des répondants (96,5 %) déclarait avoir sousrapporté les incidents de comportements perturbateurs, alors qu'un tiers (30,9 %) déclarait n'avoir jamais rapporté d'incident à la direction de l'hôpital.…”
Section: Brisons Le Silence: Rapportons Les Comportements Perturbateursunclassified
“…This report revealed that 23% of OR clinicians had personally experienced abuse and 39% had witnessed abusive behaviour. 7 In the third manuscript, published in this issue, 4 a pre-specified group of the international respondents (4,775 from seven countries) answered questions related to the reporting of disruptive behaviour to their hospital managers. Almost all respondents (96.5%) under-reported events of disruptive behaviour while one third (30.9%) never reported to hospital management at all.…”
mentioning
confidence: 99%